Comprehensive Correlation Analysis of Customer-Centric Brand Equity of Sareyn Tourist Destination - Ghasem Zarei; Mohammad Bashokouh Ajirlou; Zeynab Mahmoudi Pachal (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2018)
In a highly competitive tourism market, marketers aim to increase their brand equity by focusing on key factors as the brand equity dimensions. The degree of correlation between these dimensions makes the evaluation of tourists from one dimension also overshadow other dimensions, This issue is of particular importance in the tourist final assessment of the destination. In this regard, the present study seeks to investigate the correlation between the dimensions of the customer-centric brand equity of Sareyn tourist destination. This is an applied research and in terms of the data collection method, it is descriptive-survey. The data of 384 questionnaires which was made by the researcher has been analyzed by structural equation method using SPSS 20 and 18AMOS software. The questionnaire’s validity has been confirmed by experts and its reliability (Cronbach's alpha) for all dimensions approved. Finally, the research findings show a relatively high correlation between all the dimensions of the brand equity of Sareyn tourist destination. But the highest correlation is between perceived quality and value (0.89), and the least correlation is between image and brand perceived value (0.53). Therefore, due to the importance of these dimensions in assessing the tourists of this destination, regional tourism Managers and planners should pay more attention to promoting these dimensions and raising the level of satisfaction and as a result, increase the positive evaluation of tourists from the brand of this destination